Correction: Zhang et al. Discovery of a Ruthenium Complex for the Theranosis of Glioma through Targeting the Mitochondrial DNA with Bioinformatic Methods. Int. J. Mol. Sci. 2019, 20, 4643 - Zhang, Le; Fu, Chen; Li, Jin; Zhao, Zizhen; Hou, Yixue; Zhou, Wei; Fu, Ailing (International journal of molecular sciences, 2025)
In the original publication [...]